Digitalisation and Its Impact on Family Values and Adolescents’ Emotional Health in Community Contexts - Sri Rejeki; Rihal Jayadi; Wahyu Azwar (Universitas Pendidikan Ganesha, 2025)
This study is grounded in the increasing use of digital technology, which has the potential to influence family values and adolescents’ emotional health in the context of social change. The study aims to analyze and examine the effect of digitalization on family values and adolescents’ emotional health. A quantitative approach with a survey design was employed. The research subjects consisted of 52 adolescents who actively use digital technology. Data were collected using a Likert scale questionnaire (1–5), each comprising 10 items for the variables of digitalization, family values, and adolescents’ emotional health. The data were analyzed using descriptive statistics, normality tests, and multiple linear regression with the assistance of IBM SPSS. The results indicate that digitalization has a positive and significant effect on family values but does not have a significant effect on adolescents’ emotional health. These findings suggest that digital transformation has a greater impact on patterns of family relationships and interactions than on adolescents’ intrapersonal aspects. In conclusion, the influence of technology is contextual and shaped by broader social and psychosocial factors. The implications of this study highlight the importance of strengthening digital literacy and family based character education to optimize the benefits of technology while maintaining adolescents’ emotional balance.